In vivo effects of ketamine on glutamate-glutamine and gamma-aminobutyric acid in obsessive-compulsive disorder: Proof of concept - Rodriguez, Carolyn I. (Psychiatry Res, 2015)
We previously reported the rapid and robust clinical effects of ketamine versus saline infusions in a proof-of-concept crossover trial in unmedicated adults with obsessive-compulsive disorder (OCD). This study examined the concurrent neurochemical effects of ketamine versus saline infusions using proton magnetic resonance spectroscopy ((1)H MRS) during the clinical proof-of-concept crossover trial. Levels of the inhibitory neurotransmitter gamma-aminobutyric acid (GABA) and the excitatory neurochemicals glutamate+glutamine (Glx) were acquired in the medial prefrontal cortex (MPFC), a region implicated in OCD pathology. Seventeen unmedicated OCD adults received two intravenous infusions at least 1 week apart, one of saline and one of ketamine, while lying supine in a 3.0 T GE MR scanner. The order of each infusion pair was randomized. Levels of GABA and Glx were measured in the MPFC before, during, and after each infusion and normalized to water (W). A mixed effects model found that MPFC GABA/W significantly increased over time in the ketamine compared with the saline infusion. In contrast, there were no significant differences in Glx/W between the ketamine and saline infusions. Together with earlier evidence of low cortical GABA in OCD, our findings suggest that models of OCD pathology should consider the role of GABAergic abnormalities in OCD symptomatology.